Pengaruh Penerapan Pendekatan STEM dengan Menggunakan Google Classroom terhadap Hasil Belajar Siswa pada Materi Asam Basa - Meida Esterlina Marpaung; Dariati Dariati; Tri Santoso; Afadil Afadil (Jurnal Kreatif Online, 2022)
The study aims to determine the effect of applying the STEM approach using Google Classroom on student learning outcomes in acid-base learning. This research is quantitative experimental research with a quasi-experimental. The quasi-experimental design used in this study is a nonequivalent control group design. The sample in this study were students of class XI IPA SMA Al-Khairaat Kolono, 25 students of class XI IPA 1 and 22 students of class XI IPA 2. Data collection techniques used observation and giving tests consisting of pretest and posttest. The results of the learning activity data acquisition were the experimental class 80.4% and the control class 87.5%. This shows that the learning activities of students and teachers during the learning process are categorized as very high. The results of the student test analysis obtained a significance value from the t-test analysis of 0.002 <0.05 so it can be seen that H0 is rejected and Ha is accepted, which means that there is an effect of student learning outcomes on the application of the STEM approach to acid-base learning using Google Classroom.